Practical ambulatory anesthesia - Raeder, Johan; Urman, Richard D. (Cambridge : Cambridge University Press, 2015)
Practical Ambulatory Anesthesia covers all aspects of sedation, anesthesia, and pain relief for patients undergoing day (ambulatory) surgery. Written and edited by leading clinical anesthesiologists from the USA and Europe, it provides clear guidance on how to handle particular patients in particular situations. Comprehensive in scope, each chapter summarizes major studies and review papers, followed by practical advice based on the authors' and editors' clinical and scientific expertise. This combination of authoritative evidence-based guidance and personal advice ensures the reader benefits from the latest scientific knowledge and the authors' wealth of experience. Chapters discuss how to plan, equip and staff an ambulatory unit, pharmacology, key concepts of ambulatory care, pre- and post-operative issues, quality assurance, and current controversies. There are also dedicated chapters for topics including regional anesthesia for ambulatory surgery and pediatric ambulatory anesthesia. This text provides a much-needed comprehensive and evidence-based guide for clinical anesthesiologists.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Anesthesia; Ambulatory Surgery